The Influence Of Sales Growth And Asset Growth On Stock Return - Yulianto, Kampomo Imam; Mayasari, Mayasari (International Journal of Social and Management Studies, 2022)
The purpose of this study is to analyze the effect of sales growth and asset growth either partially or partially on stock returns. The research data was collected using secondary data from audited financial statements of issuers of the retail trade sub-sector listed on the Indonesia Stock Exchange for the 2016 - 2019 period. The sample of issuers was selected using purposive sampling so that 10 issuers were selected according to the criteria. The collected data was processed by multiple regression method with the help of SPSS 23.00 software. The results of the research show that there is a significant effect of Sales Growth on Stock Returns, there is a significant influence of Asset Growth on Stock Returns, Furthermore, simultaneously there is a significant influence on Sales Growth and Asset Growth on Stock Returns